Life as a Journey: The Spiritual Dimension in Peter Jackson's The Lord of the Rings - Garbowski, Christopher (Journal of religion and popular culture, 2004)
The article explores the problem of film's adaptation of a literary work's religious sensibility. Although some of the Christian elements of Tolkien's The Lord of the Rings remain and others have gained a different emphasis, the author maintains that the spiritual dimension of Jackson's adaptation is a more promising field for comparison. One of the major narrative metaphors in the literary and film trilogy is life as a journey; consequently, the problem of choice highlights the essential role of the conscience for human spiritual development. The journey's terminal point, death, likewise becomes a major concern, and a key to understanding the spiritual dimension of Jackson's work.